Know where you're going - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The road to a sustainable agricultural market information service (AMIS) is not necessarily very long but it is full of many steps. It is also full of many temptations which can cause its collapse. Experience in establishing and running an AMIS is...